2000
DOI: 10.1046/j.1365-8711.2000.03529.x
|View full text |Cite
|
Sign up to set email alerts
|

An H  survey of eight Abell clusters: the dependence of tidally induced star formation on cluster density

Abstract: We have undertaken a survey of Hα emission in a substantially complete sample of CGCG galaxies of types Sa and later within 1.5 Abell radii of the centres of eight low‐redshift Abell clusters (Abell 262, 347, 400, 426, 569, 779, 1367 and 1656). Some 320 galaxies were surveyed, of which 116 were detected in emission (39 per cent of spirals, 75 per cent of peculiars). Here we present previously unpublished data for 243 galaxies in seven clusters. Detected emission is classified as ‘compact’ or ‘diffuse’. From an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
128
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(135 citation statements)
references
References 62 publications
7
128
0
Order By: Relevance
“…All apart from the field comparison sample are subsets of galaxies detected as emitters of Hα and/or [Nii] lines by the Objective Prism Survey (henceforth OPS; Moss & Whittle 2000, 2005. The OPS looked at 8 low-redshift galaxy clusters, with numbers 262, 347, 400, 426, 569, 779, 1367 and 1656 in the catalogue of Abell (1958), and characterised the line emission properties of 727 galaxies from the CGCG catalogue (Zwicky & Kowal 1968, and references therein).…”
Section: Datamentioning
confidence: 99%
“…All apart from the field comparison sample are subsets of galaxies detected as emitters of Hα and/or [Nii] lines by the Objective Prism Survey (henceforth OPS; Moss & Whittle 2000, 2005. The OPS looked at 8 low-redshift galaxy clusters, with numbers 262, 347, 400, 426, 569, 779, 1367 and 1656 in the catalogue of Abell (1958), and characterised the line emission properties of 727 galaxies from the CGCG catalogue (Zwicky & Kowal 1968, and references therein).…”
Section: Datamentioning
confidence: 99%
“…Within this framework of galaxy evolution, where the environemnt plays an important role, substructure should be taken into account in seeking a global picture of the evolution of galaxies. There is thus observational evidence that a higher fraction of cluster galaxies with ongoing starburst episodes are located in substructures or in the regions of clustersubcluster interactions (Caldwell et al 1993;Biviano et al 1997;Moss & Whittle 2000;Poggianti et al 2004). Moreover, it has been observed that the presence of substructures is also directly related to the growth of the brightest cluster galaxies (BCGs).…”
Section: Introductionmentioning
confidence: 99%
“…However, the average star formation rate (SFR) in star-forming (SF) galaxies remains roughly constant with environment, and it is only the fraction of starforming galaxies that changes (Balogh et al 2004, Verdugo et al 2008, Poggianti et al 2008, Bamford et al 2008. The extent of ongoing star formation within a galaxy has also been shown to correlate with environment (Koopmann & Kenney 2004, Moss & Whittle 2000, Bamford et al 2007, implying a truncation of the star formation taking place first in the outer parts of the infalling galaxies. In fact, the last episode of star formation in cluster disc galaxies is seen to be concentrated towards the central regions (Rodríguez Del Pino et al 2014, Johnston et al 2014.…”
mentioning
confidence: 99%